Olhar(es) sobre a atenção básica : a experiência de uma entrevistadora de campo na coleta de dados do PMAQ no Estado do Espírito Santo - Zamprogno, Aline Corbellari (2013)
This work is the story of lived experience during planning, implementation and execution of the External Evaluation, integral to the National Improving Access and Quality (PMAQ) effected in the 78 municipalities of the state of Espirito Santo in 2012. This program has as its primary purpose the induction of expanding access and improving the quality of primary care, with a guarantee of a quality standard comparable national, regional and locally in order to allow greater transparency and effectiveness of government actions. Thus the essential objectives of this study are analyze the forms and conditions of the organization of primary care services, identifying facilities, difficulties and challenges. Thus, the methodological approach followed for the proposed objectives were achieved was grounded in qualitative approach, constituting an exploratory, descriptive and used as a form of design data, cartography, woven logo of fieldwork. The findings reflect a real picture of Primary Care, who showed plenty of progress, but also left sample poor sanitation and insufficient of Basic Health Units in the State of Espírito Santo.